2013
DOI: 10.1038/emboj.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 is a negative modulator of the PRC2 complex

Abstract: The Polycomb-repressive complex 2 (PRC2) is important for maintenance of stem cell pluripotency and suppression of cell differentiation by promoting histone H3 lysine 27 trimethylation (H3K27me3) and transcriptional repression of differentiation genes. Here we show that the tumoursuppressor protein BRCA1 interacts with the Polycomb protein EZH2 in mouse embryonic stem (ES) and human breast cancer cells. The BRCA1-binding region in EZH2 overlaps with the noncoding RNA (ncRNA)-binding domain, and BRCA1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 85 publications
6
124
0
Order By: Relevance
“…These observations suggest that HOTAIR regulates gene expression in the transregulatory fashion [5]. In addition, the effect of HOTAIR on EZH2 can be competed binding by BRCA1, a critical player in DNA damage response and genomic integrity [6]. HOTAIR is also shown to interact with the lysine-specific histone demethylase 1A (LSD1).…”
Section: Reviewmentioning
confidence: 93%
“…These observations suggest that HOTAIR regulates gene expression in the transregulatory fashion [5]. In addition, the effect of HOTAIR on EZH2 can be competed binding by BRCA1, a critical player in DNA damage response and genomic integrity [6]. HOTAIR is also shown to interact with the lysine-specific histone demethylase 1A (LSD1).…”
Section: Reviewmentioning
confidence: 93%
“…HOTAIR is an RNA scaffold, and the 5 0 and 3 0 domains of HOTAIR are involved in recruiting two critical epigenetic protein complexes, Polycomb Repressive Complex 2 (PRC2) and the LSD1-CoREST-REST H3K4 demethylase complex, to regulate gene expression [177]. In addition, Wang et al [178] recently found that BRCA1 can compete with HOTAIR to bind EZH2, a component of PRC2, to attenuate PRC2 activity. Therefore, loss of BRCA1 or upregulation of HOTAIR results in the reprogramming of the genome-wide PRC2-binding pattern in breast epithelial cells, leading to the altered methylation signature found in aggressive breast cancer cells [178].…”
Section: Epigenetic Regulatorsmentioning
confidence: 99%
“…In addition, Wang et al [178] recently found that BRCA1 can compete with HOTAIR to bind EZH2, a component of PRC2, to attenuate PRC2 activity. Therefore, loss of BRCA1 or upregulation of HOTAIR results in the reprogramming of the genome-wide PRC2-binding pattern in breast epithelial cells, leading to the altered methylation signature found in aggressive breast cancer cells [178]. Recently HOTAIR has been shown to be upregulated in tamoxifen-resistant breast cancer tissues compared with their primary counterparts [179].…”
Section: Epigenetic Regulatorsmentioning
confidence: 99%
“…Therefore, decreased levels of BRCA1 preclude ESC differentiation and enhance EZH2-dependent breast cancer cell migration and invasion. 89 Several long ncRNAs interact with EZH2, and their tissue-specific expression confirms the crucial role of PRC2 in organogenesis.…”
mentioning
confidence: 99%